Digital Transformation in Industry 4.0: Legal and Technological Challenges of Cloud Computing and Artificial Intelligence - Avilés, Hillary Patricia Herrera; Miranda, Juan Carlos Herrera; Pérez, Oscar Gonzalo Apaza; Larico, Juan Carlos Pinto (Journal of Ecohumanism, 2025)
Industry 4.0 has generated a revolution in production models through the use of advanced technologies such as artificial intelligence (AI) and cloud computing. However, its implementation poses significant legal and technological challenges related to privacy, cybersecurity, intellectual property and interoperability of systems. This article discusses the legal and technological challenges inherent to these technologies in the context of Industry 4.0, based on a literature review of recent research. It also proposes recommendations to address these challenges and promote safe and efficient integration.